The Influence of YouTube on Listening Skills - Cut Dara Ilfa Rahila; Muhammad Hasyimsyah Batubara; Marlina Marlina (Asosiasi Dosen Perguruan Tinggi Islam, 2023)
Listening is a crucial proficiency that learners who desire to acquire English must master. This research focused on the utilization of YouTube as a medium for improving listening proficiency. The approach in this study is a literature search process, while the literature search source is from the DOAJ portal. The data are articles about using YouTube to improve listening proficiency published in 2022-2023. The research results show that all studies conclude a significant increase in the application of YouTube media in improving students' abilities in listening. Future research regarding the use of technology in the Listening Skills aspect is needed.